Negation: An Insight into the Structure of Main Clauses in Woods Cree - Starks, Donna (Linguistica Atlantica, 1987)
Two distinct types of verbs occur in Woods Cree: the Independent and the Conjunct. Independent verbs occur in main clauses; Conjunct verbs occur in both main and subordinate clauses. Woods Cree has a number of distinct negative particles. Descriptions of Cree dialects indicate that the distinction between two of these negative particles is dependent on the inflection of the verb, mwac negates clauses with Independent verbs, lka clauses with Conjunct verbs. This paper demonstrates that in fact, the negative morphemes are independent of verb inflection. Presupposed clauses are negated with the negative particle Tka. asserted clauses with the negative particle mwac.